Effect of cryogenic treatment duration on the microhardness and tribological behavior of 40CrMoV5 tool steel. (2021) - Thakurai, Ravi; Patle, Hemendra; Ratna Sunil, B.; Dumpala, Ravikumar
Abstract: Cryogenic treatment is a potential technique to alter the properties of steels by transforming the retained austenite into martensite and by refining the carbides. The minimum content of austenite is stable enough after cryogenic treatment and during its normal service life. In the current study, cryogenic treatment was performed on the hardened 40CrMoV5 (H13) tool steel samples for different soaking periods (12, 24, 36, and 48 h). Subsequently, microstructure and microhardness of the samples were studied using optical microscopy and Vickers microhardness tester, respectively to understand the effect of the soaking time of the cryogenic treatment. The heat-treated sample exhibited the highest hardness, i.e., 772 HV, which is attributed to the presence of non-tempered martensite. The microhardness of the heat-treated sample is higher than the cryogenically treated sample due to the de-carburization of martensite content in the heat-treated sample. Among cryogenically treated, the sample with 36 h soaking time exhibited maximum hardness, (641 HV). Wear characteristics of the untreated, heat-treated, and cryogenically treated for 36 h samples were studied by using linear reciprocating tribometer. It was evident from the results that the lowest wear track width was found for a heat-treated sample as compared to the cryogenically treated sample for 36 h, and the findings are in the affirmative with the hardness values of the samples.